A review of image processing methods for fetal head and brain analysis in ultrasound images. (March 2022) - Torres, Helena R.; Morais, Pedro; Oliveira, Bruno; Birdir, Cahit; Rüdiger, Mario; Fonseca, Jaime C.; Vilaça, João L.
Highlights: A comprehensive review of image processing methods for fetal head and brain analysis in ultrasound images is provided. Five application areas: fetal head, brain structures, standard anatomical planes, development analysis, image enhancement. Division of the reviewed methods according to their theoretical approach. A detailed analysis of the methods and comparison of different approaches is provided. Identification of future research topics. Abstract: Background and objective: Examination of head shape and brain during the fetal period is paramount to evaluate head growth, predict neurodevelopment, and to diagnose fetal abnormalities. Prenatal ultrasound is the most used imaging modality to perform this evaluation. However, manual interpretation of these images is challenging and thus, image processing methods to aid this task have been proposed in the literature. This article aims to present a review of these state-of-the-art methods. Methods: In this work, it is intended to analyze and categorize the different image processing methods to evaluate fetal head and brain in ultrasound imaging. For that, a total of 109 articles published since 2010 were analyzed. Different applications are covered in this review, namely analysis of head shape and inner structures of the brain, standard clinical planes identification, fetal development analysis, and methods for image processing enhancement. Results: For each application, the reviewed techniques are categorized according to their theoretical approach, and the more suitable image processing methods to accurately analyze the head and brain are identified. Furthermore, future research needs are discussed. Finally, topics whose research is lacking in the literature are outlined, along with new fields of applications. Conclusions: A multitude of image processing methods has been proposed for fetal head and brain analysis. Summarily, techniques from different categories showed their potential to improve clinical practice. Nevertheless, further research must be conducted to potentiate the current methods, especially for 3D imaging analysis and acquisition and for abnormality detection.